Analisis Aspek Ergonomi pada Proses Pembayaran Aplikasi Klik Indomaret menggunakan Metode NASA Task Load Index (NASA-TLX) - Arini, Florentina Yuni; Saputra, Gagah Suryanatha Athallah; Putri, Farah Wahida Rizkia; Milannisya, Anya Kawakibi; Pratama, Eric Vibriano Julia; Asfino, Fadli Nugraha (JUSIFOR : Jurnal Sistem Informasi dan Informatika, 2025)
The development of information technology has influenced how consumers make transactions, including in the retail sector through online shopping applications. One widely used platform is Klik Indomaret, which provides various digital payment methods to facilitate users. This study aims to analyze the ergonomic aspects of the payment process in the Klik Indomaret application based on users’ mental workload. The study used the NASA Task Load Index (NASA-TLX) to look at six parts of mental workload: Mental Demand, Physical Demand, Temporal Demand, Performance, Effort, and Frustration. The data came from 50 active Klik Indomaret users who filled out an online questionnaire. The highest scores are found in the  Performance and Mental Demand sections, while Frustration has the lowest  score. This means users still need to pay attention and put in some effort  when making a payment, but they do not feel strong emotional pressure.  Overall, the payment process in the Klik Indomaret app is comfortable to use  and can be considered ergonomic for its users.